A study of breakfast pattern in Indonesia, Malaysia, and Philippines - Imelda Angeles Agdeppa; Ma. Rosel S Custodio; Marvin B Toledo (World Nutrition Journal, 2023)
The quality of foods taken during breakfast could contribute in shaping diet quality. The International Breakfast Research Initiative (IBRI) conducted a standardized analysis of national nutrition surveys from Indonesia, Malaysia, and the Philippines to derive nutritional recommendations for a balanced breakfast.